HIPERSEMIOTIKA: (Kritik Nalar Semiotika sebagai Teori Dusta dalam Reinterpretasi Qur'anic Studies) - Wahyu Hanafi (Institut Agama Islam Negeri (IAIN) Keiri, 2019)
This study aims to describe the distortion of semiotics as a theory of lie in the reinterpretation of the Qur'anic Studies. In Umberto Eco's view, semiotics is a discipline that studies everything that can be used to lie. That is, between what is said or written in a semiotic study doesn't match with reality. There is an asymmetric relationship between signs and reality. There is a deep gulf between a sign and referent. The concept, content, or meaning of what is spoken or written does not fit the reality described. In the interpretation of the text of the Qur'an takes a synchronic approach to know the historic meaning so the meaning of the Qur'an can be understood contextually. The actualization of semiotics as an interpretation approach of the Qur'an only touches the outside of the verses of the Qur'an textually and denies the historical meaning. So the role of semiotics in interpreting the verses of the Qur'an textually needs to be reviewed. This method of this research using descriptive qualitative method. The results of this study indicate the representation of signs in the Qur'an using the semiotics approach reap a lie based on the principles of change and transformation, imanention, language games, and simulation.